Gesture Recognition Using Artificial Neural Network - Arora, Khushboo; Suri, Shrutika; Arora, Divya; Pandey, Vaishali (International Journal of Computer Sciences and Engineering, 2014)
Information communication between two people can be done using various medium. These may be linguistic or gestures. Gestures recognition means identification and recognition of gestures originating from any type of body motion but only originate from face or hand. It is a process by which gestures made by users are used to convey the information. It provides important aspects of human interaction, both interpersonally and in the context of human - computer interfaces. There are several approaches available for recognizing gesture, some of them being MATLAB, Artificial Neural Networks, etc. This paper is a comprehensive evaluation of how gesture can be recognized in a more natural way using neural networks. It consists of 3 stages: image acquisition, feature extraction and recognition. In first stage the image is captured using a webcam, digital camera in approximate frame rate. In the second stage features are extracted using input image. The features may be angle made between fingers, no of fingers that are opened or closed or semi closed and identification of each finger. Finally neural network is used for recognition of the image.